A new species of Neosclerocalyptus Paula Couto, 1957 (Xenarthra, Glyptodontidae, Hoplophorinae) from the middle Pleistocene of the Pampean region, Argentina - Zurita, Alfredo Eduardo (2008)
A new species of the genus Neosclerocalyptus Paula Couto, 1957 (= SclerocalyptusAmeghino, 1891), N. gouldi n. sp. (Cingulata, Glyptodontidae, Hoplophorini) is described. Th is new taxon, comes from the Bonaerian Stage (middle Pleistocene; c. 0.4-0.13 Ma) of San Andrés de Giles, Buenos Aires province, Argentina. Th e type consists mainly of an associated skull, mandible and cephalic shield in an excellent state of preservation. Morphological characters that distinguish the species include: a) lesser pneumatization and lateral expansion of fronto-nasal sinuses compared to N. paskoensis; b) descending processes of maxillaries and zygomatic arches very robust and with marked ridges; c) lower third of descending processes markedly inclined toward the sagittal plane; d) inclination of the parieto-occipital skull region inter-mediate between those of Ensenadan and Lujanian forms; e) infraorbital fora mina larger than in N. paskoensis, similar in size to those of N. ornatus; and f ) occipital area less expanded laterally than in N. paskoensis. Th is new taxon completes the chronological distribution of genus Neosclerocalyptus which, until now, included two well-characterized species for the Ensenadan (early Pleistocene: N. pseudornatus and N. ornatus) and one Lujanian (late Pleistocene-early Holocene: N. paskoensis). Th e Bonaerian species, N. migoyanus, recognized by Ameghino, should be considered as a nomen dubium,due to the lack of diagnostic characters.